VP70 Structuring The Process Of Innovation Uptake In Tunisia. (2017) - Jameleddine, Mouna; Brahem, Asma Ben; Grati, Hela; Ouertatani, Hella; Allouche, Wafa; Zghal, Khaled; Asua, José; Gutiérrez-Ibarluzea, Iñaki
Abstract : INTRODUCTION: Tunisia recently implemented a Health Technology Assessment (HTA) agency (INASanté) to inform decisions around health technologies and to improve clinical practice by means of the elaboration of Clinical Practice Guidelines (CPG). However many decisions on new and emerging technologies, their implementation and coverage in the health care system are still taken at the hospital level without any structured process that informs the decisions. The aim of this project was to improve the methods and flow-chart of decision-making processes on innovation uptake in the Tunisia Healthcare System. METHODS: By means of the toolkit of EuroScan for the implementation of an early awareness and alert system (EAAS), and its checklist, it was discussed specifically within INASanté the characteristics of the Tunisia Healthcare System and its specificities regarding decisions on drugs and medical devices. The analysis included the process of innovation uptake at the hospital level and its specific flow-chart. In depth interviews and a devoted workshop were performed with personal in INASanté: two physicians (one involved in CPG elaboration and the second in accreditation), three pharmacists (HTA), one nutritionist (HTA), two librarians and other stakeholders, including the Directorate of Hospitals. RESULTS: The uptake of innovations in Tunisia does not follow a structured process. In fact, there is no central purchase of medical devices in Tunisia and most medical devices are purchased by hospitals within a tender process in accordance with the Tunisian public procurement law. The main pitfalls are: lack of awareness around innovations that could impact the system, non-structured process of information sharing among the different decision-makers that promotes inequity in access to technologies and services, and lack of explicit criteria that determine decisions around health technologies. CONCLUSIONS: Tunisia requires a structured and informed process on decisions around innovation uptake in the healthcare system. The principles that should govern this system are: anticipation of the impact of new health technologies, establishing priorities and criteria for decision making in all places of decision. The decisions should be recorded and publicly shared to avoid inequities in the access to technologies.